2002
DOI: 10.1084/jem.20011174
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism and Significance of Deletion of Parasite-specific CD4+T Cells in Malaria Infection

Abstract: It is thought that both helper and effector functions of CD4+ T cells contribute to protective immunity to blood stage malaria infection. However, malaria infection does not induce long-term immunity and its mechanisms are not defined. In this study, we show that protective parasite-specific CD4+ T cells were depleted after infection with both lethal and nonlethal species of rodent Plasmodium. It is further shown that the depletion is confined to parasite-specific T cells because (a) ovalbumin (OVA)-specific C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
123
1
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(136 citation statements)
references
References 58 publications
7
123
1
5
Order By: Relevance
“…Minor differences in HGXPRT may alter the T cell response to the protein. It is also worth noting that parasite infection is known to lead to apoptosis of human mononuclear cells (30) and of parasite-specific CD4 ϩ T cells in vivo in rodent systems (31,32). A further possibility is that HGXPRT liberated from pRBC cytoplasm into the plasma at the time of pRBC rupture may tolerize the immune system (33).…”
Section: Discussionmentioning
confidence: 99%
“…Minor differences in HGXPRT may alter the T cell response to the protein. It is also worth noting that parasite infection is known to lead to apoptosis of human mononuclear cells (30) and of parasite-specific CD4 ϩ T cells in vivo in rodent systems (31,32). A further possibility is that HGXPRT liberated from pRBC cytoplasm into the plasma at the time of pRBC rupture may tolerize the immune system (33).…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up study using antibiotic pretreated mice, the authors showed that decreased IFN-␥ production during early inflammation was correlated with an absence of the contraction phase of the primary CD8 ϩ response (5). Furthermore, using parasite-specific CD4 ϩ T cell lines another report showed that IFN-␥ indeed is involved in the depletion of effector cells during infections (31).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ~99% of parasite‐specific CD4 + T cells were lost after P. chaubadi infection 119. Another study showed that the loss of immune cells during malaria infection is unique to parasite‐specific CD4 + T cells, as ovalbumin‐specific T cells were not depleted in a murine malaria model 120. Similarly, in humans, the absolute numbers of T cells markedly increased after treatment as opposed to levels observed during concurrent infection, suggesting malaria‐induced lymphopenia 121, 122, 123, 124.…”
Section: Mechanisms Of Reduced Inflammation At High Exposure Levelsmentioning
confidence: 99%